Photoelectrochemical Properties of Platinised TiO2 - Viswanathan, B.; Sudha, K. (Asian Journal of Chemistry, 2010)
Metallization of semiconductors (Pt/TiO2) has been shown to promote redox reactions which cannot be otherwise driven by the semiconductor alone under illumination. Redox reactions can be carried out in preferred unidirections by proper metallization of the semiconductor photoanode.